Chemical Profiling of Polysaccharides Present in Peels of Citrus limetta and Bioassay based Screening of in vitro Antioxidant Activities - Adhikari, Dipan; Ghosh, Tuhin (Asian Journal of Chemistry, 2020)
In this analyses, the chemical compositions of polysaccharides isolated from the peels of Citrus limetta had been studied and discussed its antioxidant activity of different active fractions. To emphasize the chemical structure of polysaccharides, a rhamnoglucan polysaccharide was identified with probable ester linked phenolic acid. The sugar composition and purification by size exclusion chromatography (SEC) has been presented. The antioxidant capacities of the extracts prepared from Citrus limetta peel powder were determined using well known in vitro systems and standard procedure for ferric reducing antioxidant power (FRAP), 1,1-diphenyl-2-picrylhydrazyl (DPPH•), 2,2′-azino-bis(3-ethylbenzothiazoline-6-sulfonicacid) (ABTS•+), hydroxyl radical (OH•), nitric oxide (NO) assay, total antioxidant activity (TAA) and metal chelation property. The rhamnoglucan (A) present exhibited the highest bioactivity potentiality succeeded by traces of uronic acid and galactan. From the investigation, it could be emphasized that water extracted polysaccharide, which brings forth potent pharmacological activities figures out the importance as alternative natural compounds as to-be-exploited leads for low-cost sources of efficient bioactive molecules with strong antioxidant activities in different pharmaceutical and cosmoceutical formulations.